Penanggulangan Kemiskinan Berbasis Keluarga dan Komunitas : Studi Kasus Program Keluarga Harapan Di Karawang, Jawa Barat - Nugroho, Fentiny; Habibullah, Habibullah (Jurnal Ilmu Kesejahteraan Sosial, 2013)
Family Hope Program aims to break the poverty cycle by giving social assistance to families, especially very poor households. In the implementation, community participation is emphasized due to its importance for the program effectiveness. It is a fact that household-based data is used to determine the beneficiaries, however, as its objective is to cut off the intergenerational transmission of poverty, the determination of beneficiaries should use child-based data, so it can also reach street children who still have family. Family plays a central role in the program. It is expected, through intervention to poor families, their quality of life changes significantly, especially the interventions covers very important aspects, such as health and education. The community workers are specifically recruited by the Ministry of Social Affairs to carry out the program.